From Digitization to Digitalization: a Conceptual Model for Transforming the Bulgarian State Archives into a Socio-Technical Infrastructure - Chantova, Yasena (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2026)
This research puts forward a conceptual model for transforming the Bulgarian State Archives from digitization to digitalization practices. Using conceptual analysis and archival standards it identifies systemic, metadata, and AI integration layers. It argues that sustainable digital archives demand an infrastructure based on interoperability, long-term preservation, and advanced access to archival knowledge.
Keywords: Digital Archives; Digitalization; Bulgarian State Archives; Digital Cultural Heritage